Least square estimation with applications to digital signal processing - Giordano, Arthur A.; Hsu, Frank M. ([S.l.] : Wiley-Interscience, 1985)
A unified treatment of least squares based on geometric principles. Establishes the mathematical framework of least square estimation, demonstrating the utility and widespread use of these principles in a variety of digital signal processing applications. Presents new least square error algorithms supporting applications in areas such as communications, control, radar, and seismology. Provides numerous examples with algebraic steps outlined.